MAKING STUDENTS COMPREHEND NARRATIVE TEXT WITH RETELLING STRATEGY - Devrioka, Andri (English Department FBS UNP, 2015)
This paper reveals an alternative model for teaching reading narrative text using retelling strategy. Retelling is a diagnostic technique teachers use to monitor whether students are aware of text structures and if they are using this knowledge before, during, and after they read.. After reading a variety of texts, students begin to notice different ways information is presented and different patterns authors use when they write. They also recognize that the authors use different patterns to organize information. In every narrative text, there are characters, problems, a potential solution, and a final resolution. Effective readers are aware of the text structures authors use and apply this knowledge to predict what the author will write. They can also use their knowledge of the text structure of narrative to help them remember important details and to make sense of the story as they read. Keywords: retelling, narrative texts, strategy, reading comprehension